2017
DOI: 10.1371/journal.pone.0184294
|View full text |Cite
|
Sign up to set email alerts
|

Elevated aminopeptidase N affects sperm motility and early embryo development

Abstract: Aminopeptidase N (APN) is a naturally occurring ectopeptidase present in mammalian semen. Previous studies have demonstrated that APN adversely affects male fertility through the alteration of sperm motility. This enzyme constitutes 0.5 to 1% of the seminal plasma proteins, which can be transferred from the prostasomes to sperms by a fusion process. In the present study, we investigated the molecular mechanism of action of APN and its role in regulating sperm functions and male fertility. In this in vitro stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…TGM4 is involved in the formation of copulatory plugs [ 71 72 ]. ANPEP activity is associated with both sperm motility and acrosome reaction in mice and humans [ 73 74 75 76 ]. A recent study reported that GGH forms a complex with T-complex protein 1 subunit beta (CCT2) and glutathione S-transferase Mu 3 protein (GSTM-3), both involved in sperm capacitation and sperm/oocyte interaction [ 77 ], suggesting the involvement of GGH in these processes.…”
Section: Resultsmentioning
confidence: 99%
“…TGM4 is involved in the formation of copulatory plugs [ 71 72 ]. ANPEP activity is associated with both sperm motility and acrosome reaction in mice and humans [ 73 74 75 76 ]. A recent study reported that GGH forms a complex with T-complex protein 1 subunit beta (CCT2) and glutathione S-transferase Mu 3 protein (GSTM-3), both involved in sperm capacitation and sperm/oocyte interaction [ 77 ], suggesting the involvement of GGH in these processes.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence has revealed that sperm motility and motion parameters are positively correlated with early embryonic development (33). Low motility sperm may affect the acrosome reaction, and the rate of fertilization and blastocyst formation (34). Sperm with low motion parameters and motility can decrease embryo cleavage rates (35).…”
Section: Discussionmentioning
confidence: 99%
“…For ATZ-VAR group, Aminopeptidase N (AMPN) was found differential and downregulated protein expression ( Table 2 ). This multifunctional enzyme is involved in sperm regulation and fertility, as previous works have shown that increased AMPN affects sperm motility and early embryo development in mouse [ 59 , 60 ], also acting as a regulatory factor in angiogenesis in the female reproductive system [ 61 ].…”
Section: Discussionmentioning
confidence: 99%